2007
DOI: 10.1001/archsurg.142.5.461
|View full text |Cite
|
Sign up to set email alerts
|

Length of Stay

Abstract: Hypothesis: Although demographic and clinical information are known to affect hospital length of stay (LOS), we hypothesized that LOS after traumatic injury would be significantly influenced by nonclinical factors.Design: Retrospective database analysis.Patients: Trauma patients treated at hospitals participating in data submission to the National Trauma Data Bank.Methods: The National Trauma Data Bank was queried for all patients older than 18 years with an LOS longer than 48 hours and complete demographic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(57 citation statements)
references
References 27 publications
3
49
0
Order By: Relevance
“…Similar to this result, another study in one of Tehran’s hospitals showed that LOS in patients who had no insurance was less than those who paid by insurance (28). Other studies also have confirmed the relationship between method of payment and LOS (29, 30). The results of this study showed that the mean LOS was higher among patients with medical treatment compared with those with surgical intervention because general surgeries usually require less hospitalization compared with medical treatments in intensive care departments such as ICU and CCU.…”
Section: Discussionmentioning
confidence: 69%
“…Similar to this result, another study in one of Tehran’s hospitals showed that LOS in patients who had no insurance was less than those who paid by insurance (28). Other studies also have confirmed the relationship between method of payment and LOS (29, 30). The results of this study showed that the mean LOS was higher among patients with medical treatment compared with those with surgical intervention because general surgeries usually require less hospitalization compared with medical treatments in intensive care departments such as ICU and CCU.…”
Section: Discussionmentioning
confidence: 69%
“…In other patient populations, care coordination and extended care facility availability influence LOS to a large degree. 8,18 For surgical patients, emerging evidence suggests that process interventions like enhanced recovery pathways are effective at reducing LOS without increasing overall complication rates, but the efficacy of such interventions on a large scale remains unclear. 9,1922 With different uptake and implementation of enhanced recovery for colectomy patients, it would be reasonable to assume practice style differences underlie at least a portion of the unexplained variation in hospital extended LOS rates.…”
Section: Discussionmentioning
confidence: 99%
“…Within the field of trauma, several studies have shown that race and insurance are related to measures such as the likelihood of inhospital mortality, the amount of care received, and length of stay. 16 Yet despite these findings, little is known about how these factors influence the interactions of trauma patients with the health care system immediately after discharge from the hospital.…”
Section: Introductionmentioning
confidence: 99%